Air, Anggur, dan Darah: Simbolisme Yohanes dan Relevansinya dalam Teologi Katolik - Noverin Andrea Anang; Laurentius Prasetyo; Yanto Sandy Tjang (CV. ALIM'SPUBLISHING, 2026)
The study examines the theological meaning of the symbols of water, wine, and blood in the Gospel of John and their interrelation within the perspective of Catholic theology. Grounded in John’s distinctive use of symbolism as a medium of revelation, the study treats these three symbols not as isolated narrative elements but as an integrated theological sequence. The study employs a qualitative method, utilizing a literature-based approach and biblical-theological exegesis of key texts. The findings indicate that water signifies the renewal of life originating from divine grace and is closely associated with Baptism; wine expresses joy and abundance within the new covenant, finding its resonance in the Eucharist; while blood marks the culmination of divine love manifested in Christ’s redemptive sacrifice. Together, these symbols form a progressive dynamic of revelation: from renewal, to communion, and ultimately to redemption. In the light of sacramental theology, these symbols not only reveal the identity of Jesus as the incarnate Word but also mediate a concrete experience of faith within the life of the Church. Thus, the Gospel of John demonstrates that God’s salvific work unfolds in an integral and continuous manner, remaining relevant for the contemporary practice of Christian faith.